Working with families of young children with special needs - McWilliam, R. A. (New York : The Guilford Press, 2010)
This user-friendly book presents research-based best practices for serving families of children with special needs from birth to age 6. Expert contributors demonstrate how early intervention and early childhood special education can effectively address a wide range of family concerns, which in turn optimizes children's development and learning. Tightly edited, the volume offers indispensable tools for assessing families; identifying and capitalizing on their strengths; providing information, support, and coaching; collaborating with parents and teachers to address children's functional needs
Includes bibliographical references and index.
Keywords: Children with disabilities -- Education (Early childhood); Early childhood special education; Early childhood education -- Parent participation